PENGARUH JUMLAH PENDUDUK, TINGKAT INFLASI, PERTUMBUHAN EKONOMI, DAN KESEHATAN TERHADAP KEMISKINAN DI KABUPATEN MALANG - Amadea Salsabilla; Sri Muljaningsih (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Poverty is a complex and multidimensional problem. In the Malang Raya Region, poverty in Malang Regency is ranked first out of other three regions. The point of this study was to dpind out and analyze the influence of Population (JP), Inflation Rate (INF), Economic Growth (PE), and Health (KES) on Poverty in Malang Regency from 2006 to 2020. The data used are time series data obtained through the website of the Central Bureau of Statistics in East Java Province and Malang Regency. The research method used is a quantitative approach with Multiple Linear Regression Analysis. The result of this study can be conclude that variables of Population, Inflation Rate, and Economic Growth has no significant effect on Poverty. Meanwhile, the Health variable has a significant effect on Poverty in Malang Regency. Thus, Health development needs to be considered to overcome the problem of poverty.